ANALISIS PEMETAAN INDUSTRI RUMAH TANGGA BERBASIS TANAMAN PANGAN DI KOTA GORONTALO - Widyawati Katili; Wawan K. Tolinggi; Amelia Murtisari (Universitas Negeri Gorontalo, 2016)
The aim of this research is to observe area and housebold industrially production processed by using survey method. This research is conducted from June to August 2016. Data are analyzed by using descriptive analysis both qualitative and quantitative. Quantitative analysis is presented in the form of table both absolute numbers and precentages, mean qualitative analysis, the research result are presented through concepts or words to understand the flow of events in chonological order, assessing cause and effect within the scope of the local people and obtaining many useful expalantions. Research findings are (1) in Gorontalo City there are 34 household industries food palnt-based, which is divided into 15 household industries agriculture-based with the processed product is banana crackers, 9 household industries food plant-based with the processes product is cassava chips and 10 household industries agriculture-based with the processed product is corn sticks located in the villages, sub districts in Gorontalo City. (2) household industrially production with the processed product is banana crackers, with the average production is 5.133 packs in 2015 year, household industrially production with the processed product is corn sticks, with the average production is 4.250 packs in 2015 year. Keywords: Mapping, Household industries